Hubungan waiting time dengan kepuasan pasien pada pasien rawat jalan di Puskesmas - Triyoso Triyoso; Ahmad Muammar Khoddafi; Umi Romayati Keswara (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
The association between waiting time and patient satisfaction in outpatient at public health centerBackground: Patient satisfaction is one of the indicators to measure health service quality. A prolonged waiting time influences the satisfaction of a patient toward health service quality. According to the data from the health agency of pesisir barat regency in 2016, the utilization of health centers was low, it is 26.7%. the utilization was lower than the Lampang Province utilization, 32.6%.Purpose: To identify the association between waiting time and patient satisfaction in outpatient at the public health centerMethod: A quantitative method with a cross-sectional approach. The population involved 134 patients registered at Bengkunat Belimbing Health Center. The data collection was through questionnaires. The data analysis by chi square test.Results: Finding the respondents average age was 40.80 years old with a standard deviation is 8,765, the range is 19-59 years, the most of male 58 (66%), the junior secondary education 53 (60%). ), farmer occupation 56 (64%), the type of for follow up 68(77%), the variable time between waiting and registration 20 minutes 50 (57%), waiting time for registration with consultation 20 minutes 44 (50%), waiting time for consultation 20 minutes 25 (54%), overall waiting time 60 minutes 29 (63%).Conclusion: There is no significant relationship between waiting time and patient satisfaction in outpatient at the public health centerKeywords: Waiting time; Patient; Satisfaction; Outpatient; Public health centerPendahuluan: Kepuasan pasien merupakan salah satu indikator untuk mengukur kualitas layanan kesehatan. Waktu tunggu pasien lama akan mempengaruhi tingkat kepuasan pasien terhadap pelayanan. Berdasarkan Data Dinas Kesehatan Kabupaten Pesisir Barat Tahun 2016, pemanfaatan fasilitas kesehatan di Puskesmas masih rendah, yaitu 26,7% masih rendah dibandingkan pemanfaatan fasilitas kesehatan puskesmas di Provinsi Lampung yaitu 32,6%.Tujuan: Diketahui hubungan waiting time dengan kepuasan pasien di Puskesmas Bengkunat Belimbing Kab. Pesisir Barat.Metode: Penelitian kuantitatif dengan pendekatan secara cross sectional, dengan populasi seluruh pasien yang berkunjung di Puskesmas Belimbing Kab. Pesisir Barat yang berjumlah 421 responden. Tehnik pengambilan sampel dengan accidental sampling dengan jumlah sampel 134 responden. Analisa data menggunakan uji Chi Square.Hasil: Didapatkan tingkat kepuasan kategori puas berusia rata-rata 40.80 tahun dengan standar devisiasi 8.765, rentang 19-59 tahun, berjenis kelamin laki laki 58 (66%), berpendidikan SMP 53 (60%), pekerjaan petani 56 (64%), tipe kunjungan ulang 68(77%), waktu antara menunggu dengan registrasi ≥20 menit 50 (57%), waktu menunggu registrasi dengan konsultasi ≥ 20 menit 44 (50%), waktu menunggu konsultasi ≥ 20 menit 25 (54%), waktu menunggu keseluruhan ≥ 60 menit 29 (63%).Simpulan: Tidak didapatkan hubungan antara waiting time dengan kepuasan pasien (p-value >0.05)